Adolescences et identité en territoire inuit : introspections filmées - Fabienne Joliet; Laine Chanteloup; Thora Herrmann (Espace populations sociétés, 2021)
Inuit youth today faces many challenges. They live in areas integrated into globalization, which are nevertheless located on the fringes of the ecumene, grappling with geographic isolation and its consequences in terms of mobility, access to various health services, education and even of basic necessities. The young Inuit of Nunavik live in a multicultural society where the effects of colonization still mark their daily lives implying major social problems (violence, alcoholism, suicide…). However, despite this disturbing portrait that is often broadcast in the news and of which Quebec is trying to take up the challenges, young Inuit show an emerging “Inuitness”. Giving voice to this youth of Nunavik is fundamental today, since 52.8% of its population is under 24 years old.This article questions what it means to be a young Nunavimmiut today. Based on the analysis of video workshops carried out between 2016 and 2019 in 3 schools in Nunavik on their relationship to nuna (the territory in Inuktitut), 37 teenagers from 13 to 18 years old present a vision of the Arctic “from inside”, beyond the clichés. Their own video make their experience visible according to their holistic cosmology, combined with the Western dualism inherited from colonization: the persistence of an intrinsically fusional relationship with the land, resilient in its contemporary aspirations of being out on the land, spirituality, well-being, and intergenerational transmission.